Analisis Konsep Fisika Gerak Parabola Pada Permainan Bola Basket Sebagai Sumber Belajar Siswa - Dea Ananda Yulia Agustin; Aji Bagus Maulana Saputra; Defina Saghy Marspinta; Annisa Febriana Sukma; Singgih Bektiarso; I Ketut Mahardika (Peneliti.net, 2023)
Parabolic motion is a two-dimensional motion that requires quite accurate analysis to understand it. Parabolic motion is a particle movement with an initial velocity and a certain elevation angle due to the influence of the gravitational force where the particle current is in the form of a parabola. The game of basketball is an application of parabolic motion by throwing the ball into the hoop and when the mat appears to bend, this movement is a form of parabolic motion. The purpose of this research is to know the study of parabolic motion in basketball games whose techniques include passing, dribbling, and shooting. The method used in this material is descriptive qualitative with the literature review method. The results of this study are the ability to analyze the physics concept of parabolic motion in basketball games quite accurately. This is seen from the source of information conducted in this study.